Immunoadsorption treatment for dilated cardiomyopathy: A PRISMA-compliant systematic review and meta-analysis. Issue 26 (2nd July 2021) - Bian, Ru-tao; Wang, Zhen-tao; Li, Wei-yu
Abstract: Background: As one of the leading causes of heart failure, dilated cardiomyopathy (DCM) is characterized by dysfunctional muscle contraction and enlarged ventricular chamber. Patients with DCM have been shown to respond well to immunoadsorption (IA) therapies. However, the efficacy and safety of IA treatment for DCM patients remained to be evaluated. Methods: This study was designed in accordance with the Preferred Reporting Items for Systematic Review and Meta-analysis. We searched the databases such as Cochrane library, Cochrane Central Register of Controlled Trials, Embase, OVID, and Web of Science from January 1990 to March 20, 2020, and performed meta-analysis using Stata MP Version 13.0. Results: We performed meta-analysis on 12 studies that included a total of 395 patients with DCM. Overall, IA treatment significantly improved the left ventricular ejection fraction (6.01, 95% confidence interval [CI] [4.84–7.19]), reduced the left ventricular end diastolic diameter (–3.62, 95% CI [–4.06 to –3.19]), reduced severity of symptoms according to the New York Heart Association (NYHA) functional classification (–1.37, 95% CI [–1.73 to –1.02]) as compared with the controls, but had no effect on values for safety parameters (1.13, 95% CI [0.58–2.19]). Conclusions: Results of this meta-analysis indicated that the IA treatment can improve the left ventricular ejection fraction, reduce left ventricular end diastolic diameter, and thus improve clinical outcome in DCM patients. However, further evidence are required to validate the relative safety of IA treatment. Multi-center, double blind studies should be conducted to elucidate the precise effect of IA treatment in DCM patients.